Kepadatan Populasi dan Struktur Kelompok Simpai (Presbytis melalophos) serta Jenis Tumbuhan Makanannya di Hutan Pendidikan dan Penelitian Biologi (HPPB) Universitas Andalas - Rahmi Fitri; - Rizaldi; Wilson Novarino (Universitas Andalas, 2013)
A study about population density, group structure and diet of mittered leaf-monkeys (Presbytis melalophos, Raffles 1821) at the biological research and educational forest of Andalas University had been carried out from June to November 2012. This study used direct census method to figure out their structures and population and ad-libitum method to observe the plants consumed by animal subjects. There were 13 individuals of the leaf-monkeys in which belong to three groups. The group structure consisted of 2-3 adult individuals, 1- 2 subadults and 0-1 juvenile. Population density of the leaf monkeys in a defined area of 0.75 km2 was 17.3 individual/km2 and group density was 4 group/km2. The average of homerange was 0.13 km2. There were 9 species of plants consumed by the leaf monkeys within their homeranges those belong to 8 families.Keyword: Presbytis melalophos, direct census, ad-libitum, population density